2006
DOI: 10.1086/507530
|View full text |Cite
|
Sign up to set email alerts
|

Reviews Of Anti‐infective Agents: Liposomal Amphotericin B for the Treatment of Visceral Leishmaniasis

Abstract: During the past decade, liposomal amphotericin B has been used with increasing frequency to treat visceral leishmaniasis (VL). The World Health Organization convened a workshop to review current knowledge and to develop guidelines for liposomal amphotericin B use for VL. In Europe, liposomal amphotericin B is widely used to treat VL. In Africa and Asia, the VL disease burden is high and drug access is poor; liposomal amphotericin B is available only through preferential pricing for nonprofit groups in East Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
178
0
13

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(195 citation statements)
references
References 35 publications
4
178
0
13
Order By: Relevance
“…To reduce the toxicity of AmpB, lipid-based formulations have been developed (31) . A liposomal formulation (AmBisome®), an AmpB colloidal dispersion (Amphocil®), and an AmpBlipid complex (Abelcet®) have been used for the treatment of leishmaniasis (32) (Figure 2).…”
Section: Amphotericin B and Its Delivery Systems For The Treatment Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the toxicity of AmpB, lipid-based formulations have been developed (31) . A liposomal formulation (AmBisome®), an AmpB colloidal dispersion (Amphocil®), and an AmpBlipid complex (Abelcet®) have been used for the treatment of leishmaniasis (32) (Figure 2).…”
Section: Amphotericin B and Its Delivery Systems For The Treatment Ofmentioning
confidence: 99%
“…In addition, the selectivity index (SI), an indicator of the selectivity of drugs tested in in vivo models (60) , was increased by 10-fold when AmpB was added to the proposed nanodelivery system. Because the nanoparticle formulations did not cause any hemolysis of human red blood cells (31) (Table 1), the study suggested that the NQCAmpB nanoparticles could be used as an AmpB delivery system to be evaluated in in vivo models against Leishmania spp. infections.…”
Section: Optimized Nanoparticle Delivery Systems For Ampb Based On Chmentioning
confidence: 99%
“…Contrary to what was said for the conventional formulation, liposomal amphotericin B is the first-line drug for VL in Europe, USA, and other industrialized countries nowadays, offering great advantages compared to pentavalent antimonials, because of its rapid cure rates up to 100%, with a total dose of 20 mg/kg in 2e7 days, preferably 10 mg/kg once per day, on 2 consecutive days, or a total dose of 40 mg/kg, administered over 4e8 days, for immunodeficient patients, improved compliance of the patient, and reduced health care costs [173]. In HIV co-infected patients, liposomal amphotericin B is also the drug of choice both for treatment and for secondary prophylaxis, because of its efficacy and safety profile [108], while antimonials and conventional amphotericin B should be avoided due to serious toxicity and intolerance [174]. However, in poorly resourced endemic countries even short courses of liposomal amphotericin B are unaffordable, but nowadays the formulation is available at reduced price in endemic countries, and for free for selected poor countries [175].…”
Section: Amphotericin Bmentioning
confidence: 99%
“…[7][8][9] This formulation is packaged with cholesterol and other phospholipids within a small unilamellar liposome that binds to parasite ergosterol precursors, causing disruption of the parasite membrane without substantial harm to mammalian cell membranes. Additionally, the concentration of liposomal amphotericin B is high in macrophages, which enhances drug concentration in infected tissues, particularly the liver and spleen.…”
mentioning
confidence: 99%